Bioinspired Multicompartmental Microfibers from Microfluidics. (16th June 2014) - Cheng, Yao; Zheng, Fuyin; Lu, Jie; Shang, Luoran; Xie, Zhuoying; Zhao, Yuanjin; Chen, Yongping; Gu, Zhongze
<x xml:space="preserve">Abstract</x> Bioinspired multicompartmental microfibers are generated by novel capillary microfluidics. The resultant microfibers possess multicompartment body‐and‐shell compositions with specifically designed geometries. Potential use of these microfibers for tissue‐engineering applications is demonstrated by creating multifunctional fibers with a spatially controlled encapsulation of cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>